A Review of Photocatalysis using Self-organized TiO2 Nanotubes and Other Ordered Oxide Nanostructures - Paramasivam, Indhumati; Jha, Himendra; Liu, Ning; Schmuki, Patrik (Small, 2012)
Photocatalytic approaches, that is the reaction of light-produced charge carriers at a semiconductor surface with their environment, currently attract an extremely wide scientific interest. This is to a large extent due to the high expectations: i) to convert sunlight directly into an energy carrier (H2), ii) to stimulate chemical synthetic reactions, or iii) to degrade unwanted environmental pollutants. Since the early reports in 1972, TiO2 has been the most investigated photocatalytic material by far; this originates from its outstanding electronic properties that allow for a wide range of applications. Not only the material, but also its structure and morphology, can have a considerable influence on the photocatalytic performance of TiO2. In recent years, particularly 1D (or pseudo 1D) structures such as nanowires and nanotubes have received great attention. The present Review focuses on TiO2 nanotube arrays (and similar structures) that grow by self-organizing electrochemistry (highly aligned) from a Ti metal substrate. Herein, the growth, properties, and applications of these tubes are discussed, as well as ways and means to modify critical tube properties. Common strategies are addressed to improve the performance of photocatalysts such as doping or band-gap engineering, co-catalyst decoration, junction formation, or applying external bias. Finally, some unique applications of the ordered tube structures in various photocatalytic approaches are outlined.
EAM Import::2019-03-13